A Comparative Study of Systems Pharmacology and Gene Chip Technology for Predicting Targets of a Traditional Chinese Medicine Formula in Primary Liver Cancer Treatment - Li, Songzhe; Sun, Yang; Sun, Yue (Frontiers in Pharmacology, 2022)
Background: The systems pharmacology approach is a target prediction model for traditional Chinese medicine and has been used increasingly in recent years. However, the accuracy of this model to other prediction models is yet to be established. Objective: To compare the systems pharmacology model with experimental gene chip technology by using these models to predict targets of a traditional Chinese medicine formula in the treatment of primary liver cancer. Methods: Systems pharmacology and gene chip target predictions were performed for the traditional Chinese medicine formula Zhenzhu Xiaoji Tang (ZZXJT). A third square alignment was performed with molecular docking. Results: Identification of systems pharmacology accounted for 17 % of targets, while gene chip-predicted outcomes accounted for 19 %. Molecular docking showed that the top ten targets (excluding common targets) of the system pharmacology model had better binding free energies than the gene chip model using two common targets as a benchmark. For both models, the core drugs predictions were more consistent than the core small molecules predictions. Conclusion: In this study, the identified targets of systems pharmacology were dissimilar to those identified by gene chip technology; whereas the core drug and small molecule predictions were similar.